Safe bicycle riding scales based on the transtheoretical model for adolescents: Development and validation - ERDEM, ÖZDEN; EROL, SAİME (ELSEVIER SCI LTD, 2021)
Background: Deaths from bicycle transport have increased by 30% in the past 10 years. This should be considered a problem from various aspects for this reason. Safe bicycle riding concerns not just wearing a helmet; it involves a wide range of matters that must be considered. Methods: The universe of the study, which is of development and validation design, consisted of fifth, sixth, seventh and eighth grade students (N = 503) enrolled in a middle school located in Istanbul during the 2017?2018 academic year. The data were collected with a 25-item questionnaire on sociodemographic features and bicycle riding behavior, and the Transtheoretical Model of scales. The adolescents in the study group were between the ages of 9?14; 49.5% were female, 50.5% were male. Used in testing for validity and reliability were the Content validity index, exploratory factor analysis, confirmatory factor analysis, floor-ceiling effect, Hotelling?s T2, Standard Error of Measurement, the paired sample t-test, and Pearson?s correlation. Results: The internal consistency reliability coefficients of the scales are ? = 0.79 for the Cognitive Change Process Scale, ? = 0.82 for the Behavioral Change Process Scale, ? = 0.77 for the Pros Scale of Decisional Balance, ? = 0.79 for the Cons Scale of Decisional Balance, ? = 0.78 for the Self?Efficacy Scale. It was found that the Cons Scale of Decisional Balance mean score was under average, all other scale mean scores were above the average. Of the adolescents, 24.5% were in the precontemplation stage of change regarding safe bicycle riding in the Transtheoretical Model. Conclusions: Adolescents? safe bicycle riding behaviors can be evaluated by using scales that are valid and reliable. With the interventions to be implemented, changes can be achieved in safe bicycle riding behaviors and these changes can be screened with the Transtheoretical Model scales.
Keywords: Bicycle; Scale; Adolescent; Cycling; Transtheoretical model